1978
DOI: 10.1159/000232051
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Allergic Reactions by Cromoglycate and by a New Anti-Allergy Drug U-42,585E

Abstract: A new inhibitor of IgE-mediated allergic reactions has been studied in rats. This new inhibitor is chemically different from cromoglycate and shows qualitative and quantitative advantages over it. It is 2,500 times more active in rats than disodium cromoglycate and shows oral activity. This new inhibitor possesses no bronchodilator or end-organ antagonism activity and does not raise intracellular cAMP levels but as cromoglycate acts by inhibition of mediator release. Multiple high (25 mg/kg) doses in rats lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 8 publications
(10 reference statements)
1
22
0
Order By: Relevance
“…The incomplete blockade of APNEA by sodium cromoglycate and lodoxamide remains to be explained. It is, however, entirely consistent with in vitro findings where mediator release inhibition is often incomplete and may show a bell-shaped doseresponse relationship (Johnson et al, 1978;Tanizaki et al, 1992). defining the role of the mast cell in a variety of experimental circumstances (see, for example, Di Rosa et al, 1971;Banks et al, 1990 the A3 receptor-mediated component of the response to AP-NEA, neither increased histamine levels per se nor modified the response to APNEA, mediator release can be unequivocally attributed to the effects of APNEA.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The incomplete blockade of APNEA by sodium cromoglycate and lodoxamide remains to be explained. It is, however, entirely consistent with in vitro findings where mediator release inhibition is often incomplete and may show a bell-shaped doseresponse relationship (Johnson et al, 1978;Tanizaki et al, 1992). defining the role of the mast cell in a variety of experimental circumstances (see, for example, Di Rosa et al, 1971;Banks et al, 1990 the A3 receptor-mediated component of the response to AP-NEA, neither increased histamine levels per se nor modified the response to APNEA, mediator release can be unequivocally attributed to the effects of APNEA.…”
Section: Discussionsupporting
confidence: 84%
“…Since APNEA is relatively non-selective , the A3 receptor component of the cardiovascular response was effectively 'isolated' by pretreatment of animals with the broad spectrum adenosine receptor antagonist, 8-SPT, at a dose well in excess of those required to antagonize A1, A2A and A2B receptors in this preparation (Fozard & Carruthers, 1993a,b; see also (Brogden et al, 1974;Johnson et al, 1978). Dose-dependent blockade of the response to APNEA by both com- pounds with lodoxamide being clearly the more potent would thus be consistent with a role for mast cells in the response to APNEA.…”
Section: Discussionmentioning
confidence: 99%
“…Addi tional blockers of the respiratory response to Ascaris have been described [Johnson and Van Hout, 1976;Johnson et al, 1978Johnson et al, , 1979, Recently, a prostacyclin analog, U-60,257 Piriprost, was found to be a selec tive inhibitor of leukotriene C and D synthesis in vitro [Bach et al, 1982],…”
Section: Introductionmentioning
confidence: 99%
“…Ascaris antigen (AA) induced bronchoconstriction in monkeys has been useful for the determination of preclinical anti-asthmatic activity of investigational anti-allergic compounds [1][2][3][4], In these studies, bron choconstriction was measured in anesthetized, spon taneously breathing monkeys after inhalation of mists generated from AA solutions of predetermined con centrations.…”
Section: Introductionmentioning
confidence: 99%